The isoflavonoid tectorigenin has better antiplatelet potential than acetylsalicylic acid - Applová, Lenka; Karlíčková, Jana; Říha, Michal; Filipský, Tomáš; Macáková, Kateřina; Spilková, Jiřina; Mladěnka, Přemysl (Phytomedicine, 2017)
BACKGROUND: One reason for the lower incidence of cardiovascular diseases in Asian countries may be the high intake of isoflavonoids and their antiplatelet effects may be an important factor. To date, there is limited comparison of a range of isoflavonoids and knowledge of their effects at different levels of platelet aggregation. PURPOSE: To screen the antiplatelet effects of a number of isoflavonoids on the arachidonic acid based aggregation pathway and investigate how the antiplatelet activity might occur. METHODS: The antiplatelet effects were first screened in whole human blood where platelet aggregation was induced by arachidonic acid. Further analysis was targeted at search of the mechanism of action. RESULTS: Thirteen of the eighteen tested isoflavonoids had significant inhibitory effect on platelet aggregation in whole human blood. Genistein had the same potency as clinically used acetylsalicylic acid (ASA) while tectorigenin was clearly stronger than ASA. Further analyses showed that the effect of tectorigenin was not based on inhibition of cyclooxygenase-1 in contrast to ASA or thromboxane synthase but by competitive antagonism at thromboxane receptors. CONCLUSION: Tectorigenin is a more potent antiplatelet compound than ASA and thus an interesting substance for further testing.
Keywords: Platelet Aggregation; inhibitory agregace trombocytů; Humans; lidé; Isoflavones; Platelet Aggregation Inhibitors; cyklooxygenasa 1; isoflavony; Genistein; Cyclooxygenase 1; Aspirin; agregace trombocytů; genistein